Bioaktivitas In Vitro Ekstrak Etanol Biji Pinang terhadap Jamur Candida albicans - Asrianto, Asrianto; Asrori, Asrori; Sahli, Indra Taufik; Hartati, Risda; Mulyani, Wiwiek (Health Information : Jurnal Penelitian, 2022)
Areca nut (Areca catechu L) is traditionally used to treat wounds and bleeding, urinary tract infections, leg pain, and worms. Modern research studies, the areca nut has a pharmacological effect as an antifungal. This study aims to determine the ability of the ethanol extract of areca nut to the growth of the fungus Candida albicans. This research is experimental research. The steps are taken in this study, firstly, the peeled areca nut seeds were dried in the sun for 7-10 days. After drying, crushed into powder. Furthermore, the phytochemical extraction process uses the maceration method using ethanol. Extracts were obtained using a rotary vacuum evaporator. The extracts obtained were made in series with concentrations of 20, 40, 60, and 80 g/ml. Each concentration series was tested for antifungal inhibition using the Kirby Bauer method. The clear zone formed was measured using a calliper. The data were analyzed using non-parametric Kruskal Wallis statistics and Mann-Whitney U test. The results of the inhibitory test of areca nut ethanol extract showed descriptively that the ethanol extract had the inhibitory ability against the fungus C. albicans. Statistical analysis of all concentration levels gave a significant effect in inhibiting fungal growth. Further tests showed that the concentrations of 20 g/ml and 80 g/ml as well as 60 g/ml and 80 g/ml had a significance value of <0.05, which means that there were different effects in inhibiting the growth of the fungus C. albicans. This study concludes that the ethanol extract of areca nut seeds can inhibit the growth of the fungus C. albicans.